Transforming Gender Relations and Reducing Risk of Zoonotic Diseases among Small Ruminant Farmers in the Highlands of Ethiopia - Wieland, Barbara; Mulema, Annet; Kinati, Wole; Woldegiorgis, Mamusha; Mekonnen, Mesfin; Alemu, Biruk; Desta, Hiwot; Demeke, Yifru; Elias, Belay (2024)
Community conversations were piloted in four villages located in three woredas (districts) of Ethiopia - Doyogena district in Southern Nations, Nationalities, and Peoples’ Region (SNNPR), Menz Gera Midir, and Menz Mama Midir (referred to as Menz districts) in the Amhara region. These are sites where the CGIAR (Consultative Group on International Agricultural Research) Research Program on Livestock implements livestock research interventions to improve the livelihoods of smallholder livestock producers. The sites were selected based on their livestock density, market access, and ethnicity. Alongside these conversations individual interviews were conducted before and after the community conversations (the intervention) using a semi-structured questionnaire to determine knowledge, attitude, and practice of community members regarding division of labor, ownership, and control of livestock resources; institutions and structures; and management of zoonoses. We interviewed about 20 individuals from randomly sampled households in each village at the location conversations where held, yielding 83 respondents (47 men and 36 women). Participants responded to statements on a Likert scale range of agreeing, neutral, and disagreeing. Reasons for their ratings were also recorded. For this activity we partnered with the Doyogena and Menz Gera Woreda Offices of Livestock Development.